State Railway of Thailand Employee Performance: A Structural Equation Model Analysis - Sivalai, Tanin (Animo Repository, 2018)
Dropping from a peak of 88 million riders in 1994, Thailand’s state railway system today is only transporting 35 million passengers annually. Operations run at a loss, with infrastructure and aged equipment contributing to significant delays, and a continuing loss of passengers. However, in September 2017, a new 20-year US$81.57 billion plan was introduced to save the State Railway of Thailand [SRT] from its death spiral. Given the magnitude of the problem, this study aims to analyze employee performance of SRT civil servants. Using multi-stage random sampling, 360 individuals were selected; through a five-level, Likert type agreement scale questionnaire, 54 items concerning their characteristics, their perspectives on SRT’s organizational culture, human resource management processes, the SRT’s total quality management program, and their effect on employee performance were analyzed. From the data, LISREL 9.1 was used to conduct a confirmatory factor analysis and structural equation model to analyze the results. The structural equation model [SEM] results showed that all the causal factors in the model were shown to have a positive influence on SRT employee performance, which is explained by the variance of factors influencing SRT employee performance (R2) by 92%. Ranked in importance, the results determined that human resources [HR=0.96], had the most significant impact on employee performance [EP], followed by total quality management [TQM=0.45], and finally, organizational culture [OC=0.37].